Catalogue and typifications of new taxa of vascular plants described by Finnish botanist Harald Lindberg (1871–1963) - Väre, Henry (Phytotaxa, 2012)
As a taxonomist Harald Lindberg mainly worked on North European and Mediterranean vascular plants. He published about 420 valid names of new taxa and in addition numerous invalid names or nomina nuda. In the present catalogue all the new names except those published under the apomictic genera Hieracium and Taraxacum, or names of mosses, are listed. Most of the North European new taxa are based on material collected by himself or others in Finland or adjacent Russia, rarely from Estonia or Sweden. The Mediterranean taxa are mostly based on the collections by his own hand from Croatia, Cyprus, Italy, Morocco, Spain or Tunisia, rarely from Bosnia and Herzegovina, Egypt, Hungary, Montenegro or Tunisia. Lindberg had no concept of type specimens and therefore all his taxa needed lectotypification. Most of the lectotypifications are performed in the present catalogue. Lindberg’s main collections are preserved in the Botanical Museum, Finnish Museum of Natural History, University of Helsinki, Finland (H). Numerous types are represented in the exsiccata series Plantae Finlandiae Exsiccatae (nos. 1–2081) that Lindberg edited and distributed to other herbaria in 42 fascicules. His Mediterranean types specimens are frequently duplicated in the herbaria of Kew (K), Lund (LD) and/or Montpellier (MPU). Many of the names provided by Lindberg were validated by other authors, especially by I. Hiitonen in his Suomen Kasvio (1933). Many of the new taxa by Lindberg describe forms and varieties that are nowadays rarely recognized even though they are usually not based on obvious environmental modifications. In total, Lindberg described 321 vascular plant names Hieracium (34 taxa) and Taraxacum excluded (65). With these genera the total number is 420.